Seasonal dynamics of soil microbial growth, respiration, biomass, and carbon use efficiency in temperate soils - Schnecker, Jörg; Baldaszti, Ludwig; Gündler, Philipp; Pleitner, Michaela; Sandén, Taru; Simon, Eva; Spiegel, Felix; Spiegel, Heide; Urbina Malo, Carolina; Zechmeister-Boltenstern, Sophie; Richter, Andreas (Geoderma, 2023)
Soil microbial growth, respiration, and carbon (C) use efficiency (CUE) are essential parameters to understand, describe and model the soil carbon cycle. While seasonal dynamics of microbial respiration are well studied, little is known about how microbial growth and CUE change over the course of a year, especially outside the plant growing season. In this study, we measured soil microbial respiration, gross growth via ¹⁸O incorporation into DNA, and biomass in an agricultural field and a deciduous forest 16 times over the course of two years. We sampled soils to a depth of 5 cm from plots at which harvest residues or leaf litter remained on the plot or was removed. We observed strong seasonal variations of microbial respiration, growth, and biomass. All these microbial parameters were significantly higher at the forest site, which contained 4.3 % organic C compared to the agricultural site with 0.9 % organic C. CUE also varied strongly (0.1 to 0.7) but was overall significantly higher at the agricultural site compared to the forest site. We found that microbial respiration and to a lesser extent microbial growth followed the seasonal dynamics of soil temperature. Microbial growth was further affected by the presence of plants in the agricultural system or foliage in the forest. At low temperatures in winter, both microbial respiration and gross growth showed the lowest rates, whereas CUE (calculated from both respiration and growth) showed amongst the highest values determined during the two years, due to the higher temperature sensitivity of microbial respiration. Microbial biomass C strongly increased in winter. Surprisingly, this winter peak was not connected to high microbial growth or an increase in DNA content. This suggests that microorganisms accumulated C and N, potentially in the form of osmo- or cryoprotectants or increased in cell size but did not divide. This microbial winter bloom and following decline, where C is released from microbial biomass and freely available, might constitute a highly dynamic time in the annual C cycle in temperate soil systems. Highly variable CUE, which was observed in our study, and the fact that CUE is calculated from independently controlled microbial respiration and microbial growth, ask for great caution when CUE is used to describe soil microbial physiology, soil C dynamics or C sequestration. Instead, microbial respiration, microbial growth, and microbial biomass C should be investigated individually in combination to better understand the soil C cycle.